The Development Of Interactive E-modules Integrated With Ethnoscience On Temperature, Heat, and Expansion - Suryani, Refzi Irma; Diliarosta, Skunda (Universe, 2025)
The study aims to determine the validity and practicality of interactive e-modules integrated with Ethnoscience on temperature, heat, and expansion materials. This research is a Research and Development (R&D) with ADDIE’s development model. The instrument used in this study were validity and practicality questionnaires. The interactive e-module was validated by expert validators using a validity questionnaire. The practicality test was conductedby teachers and students using a practicality of the product was obtained with an average validity of 0.88 in the high very category. The average value of the practicality of using interactive e-modules integrated with Ethnoscience according teachers and students is 0.96 and 0.93 respectively in the very high category. So it can concluded that the Ethnoscience integrated interactive e-module on temperature, heat, and expansion material is valid and practical to use.